Positive effects of lower extremity constraint-induced movement therapy on balance, leg strength and dual-task ability in stroke patients: a longitudinal cohort study - Annika Sefastsson; Ingela Marklund; Håkan Littbrand; Per Wester; Britt-Marie Stålnacke; Ann Sörlin; Birgitta Langhammer; Per Liv; Xiaolei Hu (Medical Journals Sweden, 2024)
Objective: To investigate whether high-intensity lower extremity constraint-induced movement therapy can improve balance, leg strength, and dual-task ability. Design: A longitudinal cohort study in a real-world outpatient clinic. Patients: 147 community-dwelling participants in the subacute and chronic poststroke phases. Methods: Participants received lower extremity constraint-induced movement therapy for 6 hours/day during 2 consecutive weeks, including balance, strength, and functional training. The Berg Balance Scale (BBS), Single-Leg-Stance (SLS) bilaterally, one Repetition Maximum (1RM) in a leg press, symmetry of leg strength (Diff-1RM), Timed Up and Go (TUG), and the TUG Manual test were assessed before, after, and 3 months after lower extremity constraint-induced movement therapy. Results: Compared with preintervention data, statistically significant improvements after lower extremity constraint-induced movement therapy (p < 0.001) were demonstrated for balance with an absolute value in BBS at 1.9 points (effect size 0.38) and SLS at 2.4 s (effect size 0.24), and for leg strength at 10.2 kg (effect size 0.54) for the affected leg. Diff 1RM decreased significantly at 5.8 kg (effect size 0.39) and improvements on dual-task ability at 2.7 s were significant (effect size 0.14). The effects persisted at the 3-month follow-up. Conclusions: High-intensity lower extremity constraint-induced movement therapy may be a feasible treatment option for middle-aged stroke patients to affect balance, leg strength, and dual-task ability positively in an out-patient clinical setting.